Práticas integrativas e complementares na promoção da saúde de servidores públicos federais: contribuições da terapia Reiki - Lemos, Liris Léa (2019)
Integrative and Complementary Practices (PICs) have been distinguished by their expanded vision of the health-disease-care process, by the demedicalization of health care and by the contributions to self-care and autonomy. The incorporation of PICs in the care process is directly related to the changes in the field of public health and to the strengthening of health promotion proposals. In the context of health care for federal civil servants, PICs have been incorporated as strategies for health promotion. The general objective of the study was to analyze the motivations of federal educational institution servers for the use of Reiki Therapy and the contributions of the integrative practice for the promotion of worker health. Reiki is a practice of Japanese origin of laying hands on the body in order to stimulate the natural mechanisms of health recovery and promote harmonization between the physical, mental and spiritual dimensions. The research scenario is a unit of reference of the Integrated Subsystem of Attention to Health of the Server (SIASS) linked to the federal university of the Southeast Region. The research participants were 24 users of Reiki Therapy in attendance at the SIASS Unit. It is a study with a qualitative methodology developed using a questionnaire to characterize the participants and semi-structured interviews. Thematic analysis guided the treatment of data and the construction of two categories: Different understandings of health; Reiki in the SIASS Unit. Among the participants were women (80%), people aged between 31 and 60 years (80%), union (50%), catholics and spiritist (42%), and higher education (72%). (58%) and worked 40 hours a week (82%).Servers use Reiki in a complementary and integrative way to other care practices. The study allowed the mapping of critiques to the biomedical model and identification of different medical rationalities in the health field. Participants criticized the allopathic and biomedical forms of care and the lack of attachment and empathy of some health professionals. The motivations for seeking Reiki relate to the health conditions of the workers, the positive reports of other users and the offer of therapy in the SIASS Unit. The benefits reported were: improvements in health conditions, building links with therapists, feeling of peace and tranquility, and support for self-knowledge. The study revealed that the insertion of Reiki therapy into the SIASS Unit guarantees accessibility to PICs, increases the possibilities of care for the federal public servant and contributes to the demedicalization of health care.